Analisis Anatomi dan Trikoma Tanaman Obat Dandang Gendis Clinacanthus nutans (Burm. f.) Lindau - Elis Tambaru; Samuel A Paembonan; Resti Ura'; Mustika Tuwo (Universitas Hasanuddin, 2019)
Research on the analysis of the anatomy of the stomatal and trichomes of the medicinal plant Dandang Gendis Clinacanthus nutans (Burm.f.) Lindau in Makassar City. This study aims to determine the anatomical structure of the stomatal and trichomes of longitudinal cross-section of leaves that are used as herbal medicines. This research method was used to spread acetone to obtain stomatal prints on the leaf surface, the data were analyzed descriptively. The results of the analysis of the anatomy of the stomatal and trichomes of leaves of the medicinal plant Dandang Gendis Clinacanthus nutans (Burm.f.) Lindau was a diacytic type of stomatal, the spread of stomatal was only found on the surface of the abaxial leaf including the apple type. The number of abaxial stomatal was 160 stomatal/mm2. The number of epidermal cells was 748 epidermis/mm2 and abaxial 504 epidermis/mm2, stomatal index 23.95%, and stomatal size 159.26 µm. On the adaxial and abaxial surfaces of the leaves of Dandang Gendis Clinacanthus nutans (Burm.f.) Lindau, glandular and lithocyst trichomes were encountered.